Макро- та мікроструктура фразеологічних тлумачних словників української мови ХХ ст.: теоретичне підґрунтя, засади, форма - Цимбалюк-Скопненко, Т. (Лексикографічний бюлетень, 2018)
The article analyses the compilation of dictionaries of explanatory type. It is important for a phraseographer not only to correctly outline the semantic volume of a stable phrase, but also to determine its stylistic parameters. The considered dictionaries have laid the foundation of academic phraseography, without considering their principles of conclusion it is impossible to understand modern approaches to the description of phrasematic material.Each of them deserves a separate exploration, which can show the achievements and miscalculations of the compilers, but for the author of this article the main task was to show the direction of phraseological thought from unstructured material to conscious construction of macro-, media- and microstructure phraseological dictionary of the Ukrainian language.